2021
DOI: 10.1038/s41598-021-87103-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits linked to pathogen prevalence in wild bee communities

Abstract: Reports of pollinator declines have prompted efforts to understand contributing factors and protect vulnerable species. While pathogens can be widespread in bee communities, less is known about factors shaping pathogen prevalence among species. Functional traits are often used to predict susceptibility to stressors, including pathogens, in other species-rich communities. Here, we evaluated the relationship between bee functional traits (body size, phenology, nesting location, sociality, and foraging choice) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
(72 reference statements)
2
2
0
Order By: Relevance
“…and Lasioglossum immunitum ) and social bees ( Halictus spp., Apis mellifera and B. terrestris ) and also non-hymenopteran insects such as grasshoppers (C alliptamus italicus ) . Although there is a wide variety in the functional traits of the insects studied, such as body size, phenology, nesting location, sociality and/or diet, which could influence pathogen prevalence [ 43 ], our data support earlier findings that trypanosomatid infection [ 38 , 43 45 ] can occur in both social and solitary species. For example, the α-tubulin TaqMan assay described herein detected for the first time trypanosomatid infection in bees belonging to the genus Amegilla , namely in a wild solitary bee also known as the white-banded Digger Bee.…”
Section: Discussionsupporting
confidence: 88%
“…and Lasioglossum immunitum ) and social bees ( Halictus spp., Apis mellifera and B. terrestris ) and also non-hymenopteran insects such as grasshoppers (C alliptamus italicus ) . Although there is a wide variety in the functional traits of the insects studied, such as body size, phenology, nesting location, sociality and/or diet, which could influence pathogen prevalence [ 43 ], our data support earlier findings that trypanosomatid infection [ 38 , 43 45 ] can occur in both social and solitary species. For example, the α-tubulin TaqMan assay described herein detected for the first time trypanosomatid infection in bees belonging to the genus Amegilla , namely in a wild solitary bee also known as the white-banded Digger Bee.…”
Section: Discussionsupporting
confidence: 88%
“…and Lasioglossum immunitum) and social bees (Halictus spp., Apis mellifera and Bombus terrestris) but also in non-hymenopteran insects such as grasshoppers (Calliptamus italicus). Although there is wide variety of functional traits such as body size, phenology, nesting location, sociality, and/or diet that could in uence pathogen prevalence [39], this data supports that trypanosomatid infection could occurs either in social or solitary species as it was previously reported [34,[39][40][41]. For instance, the α-tubulin TaqMan assay detected for the rst time trypanosomatid infection in the genus Amegilla, a wild solitary bee also known as white-banded Digger Bee.…”
Section: Discussionsupporting
confidence: 85%
“…In the continental United States, many studies have reported Crithidia rates in bumble bee species. There is substantial variation both within and across species, as well as across space and time, with estimates ranging from 0% to 82% infected (Cordes et al, 2012; Figueroa et al, 2021; Gillespie, 2010; Malfi & Roulston, 2014). A nationwide survey comparing C. bombi rates across 36 species in the United States reported that C. bombi prevalence was usually lower than 10% for the majority of bumble bee species, but highest in B. mixtus and B. impatiens populations (32%, N = 68; 26.7%, N = 45, respectively).…”
Section: Discussionmentioning
confidence: 99%